Thoracoscopic treatment of primary spontaneous pneumothorax without a drainage tube in male patients. Issue 2 (February 2023) - Fu, Honghao; Jin, Defeng; Wei, Yutao
Objective: To propose a treatment approach for primary spontaneous pneumothorax (PSP) in male patients with a smaller incision and less pain. Methods: We retrospectively studied 29 patients with PSP who underwent areola-port video-assisted thoracoscopic surgery (VATS) and 21 patients who underwent single-port VATS. The areola-port VATS technique was performed as follows. First, an arc incision was made along the lower edge of the areola, and a 5-mm-diameter thoracoscope was placed. The bullae were completely removed, and the absence of air leaks and other bullae was confirmed. A drainage tube was placed in the chest with negative pressure and then quickly pulled out, and the reserved suture line was knotted. Results: All patients were male, and their mean age was 19.07 ± 2.43 years. The mean intraoperative hemorrhage volume and postoperative pain score were significantly lower in the areola-port than single-port group. The mean operative time and mean postoperative hospital stay were also shorter in the areola-port group, but without statistical significance. The incidence of complications and the 1-year postoperative recurrence rate were 0% in both groups. Conclusion: Our method is clinically feasible and inexpensive, has a traceless effect, and is especially suitable for adolescents.